Primary and secondary mucosal melanoma of the small intestine – a clinical, pathological, and genetic nationwide survey of Danish patients between 1980 and 2014. Issue 9 (29th August 2018) - Tingsgaard, Jakob Koefoed; Henriksen, Amalie; Mikkelsen, Lauge Hjorth; Behrendt, Nille; Melchior, Linea Cecilie; Svendsen, Lars Bo; Heegaard, Steffen
Abstract : The aim of this study was to describe the epidemiology, symptomatology, pathology, genetics, and treatment of primary and metastatic small intestine melanoma in a national Danish cohort. All Danish patients diagnosed with small intestinal melanoma during the period 1980–2014 were included. For each patient, clinical data along with available pathology report and tissue was registered. Targeted next‐generation sequencing (NGS) of known hotspots in 50 oncogenic genes was performed. Twenty patients with small intestinal melanoma were retrieved. Eight of these were primary melanomas. The median age was 66 years for primary melanoma patients and 58 years for secondary melanoma patients. The male/female ratio (M/F) was 3:1 for primary melanoma and 1:1 for secondary melanoma. The median time of survival was 3.5 months and 9 months for primary and secondary melanoma patients, respectively. NGS of primary tumours showed polymorphisms in the HRAS, PI3KCA, and JAK3 genes. Primary mucosal melanoma of the small intestines is a very rare disease, with an incidence of 0.04 cases/million/year in Denmark. Patients aged 59–70 years with abdominal symptoms should make the clinician consider a small bowel melanoma as a differential diagnosis. The prognosis ranged from less than a month to 183.6 months.